2004
DOI: 10.1359/jbmr.0301241
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Unloading Induces Resistance to Insulin-Like Growth Factor-I (IGF-I) by Inhibiting Activation of the IGF-I Signaling Pathways

Abstract: We showed that unloading markedly diminished the effects of IGF-I to activate its signaling pathways, and the disintegrin echistatin showed a similar block in osteoprogenitor cells. Furthermore, unloading decreased ␣V␤3 integrin expression. These results show that skeletal unloading induces resistance to IGF-I by inhibiting activation of the IGF-I signaling pathways at least in part through downregulation of integrin signaling. Introduction:We have previously reported that skeletal unloading induces resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 57 publications
8
107
1
Order By: Relevance
“…We recently showed that fluid shear stress synergizes with IGF-I to stimulate Erk1/2 activation and osteoblast proliferation through integrin-dependent activation of the IGF-I signaling pathway (28), confirming a functional role of the IGF-I signaling pathway in the mechanical stimulation of osteoblast proliferation. Bikle and co-workers (26,27) have also demonstrated that skeletal unloading induces resistance to IGF-I to induce bone formation, which is caused by inhibition of the IGF-I signaling pathway through down-regulation of the integrin pathway. Regarding the ER signaling pathway, Lanyon and co-workers (25,(43)(44)(45)(46) have provided compelling evidence that ER, especially ER␣, is essential for mechanical stimulation of bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that fluid shear stress synergizes with IGF-I to stimulate Erk1/2 activation and osteoblast proliferation through integrin-dependent activation of the IGF-I signaling pathway (28), confirming a functional role of the IGF-I signaling pathway in the mechanical stimulation of osteoblast proliferation. Bikle and co-workers (26,27) have also demonstrated that skeletal unloading induces resistance to IGF-I to induce bone formation, which is caused by inhibition of the IGF-I signaling pathway through down-regulation of the integrin pathway. Regarding the ER signaling pathway, Lanyon and co-workers (25,(43)(44)(45)(46) have provided compelling evidence that ER, especially ER␣, is essential for mechanical stimulation of bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, lack of reduction in bone formation by the loss of mechanical stress in the absent of OPN would be resulted in part in the loss of signals for differentiation of osteoblastic precursor cells in bone marrow cells. Recent data revealed that unloading induces resistance to insulin-like growth factor-I (IGF-I) by inhibiting activation of the IGF-I signaling pathways through down-regulation of a v b 3 integrin in bone marrow cells (Sakata et al 2004). IGFbinding protein-5 (IGFBP-5), which is one of the six forms of IGFBPs, binds to OPN, and these interactions are considered to modulate the cooperative actions between the IGF-I receptor and integrin receptor signaling pathways (Nam et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma was obtained from blood from the facial vein of mice after 3-h fasting at the indicated age. P1NP and CTX were measured by using ELISA kits (Biomedical Technologies and Immunodiagnostic Systems), respectively (41,42,49). Alkaline phosphatase was measured on a Randox Daytona analyzer (Randox Laboratories Limited) at the General Clinical Research Center of Indiana University School of Medicine.…”
Section: Methodsmentioning
confidence: 99%